Creating built environments : bridging knowledge and practice divides - Lawrence, Roderick J. (New York, NY : Routledge, 2021)
"Built environments are multidimensional and need to be understood by careful analysis. They should be understood before reconsidering how professionals of the built environment should be educated and trained to reduce the gap between knowledge, practice and real-world circumstances. There is an urgent need to rethink the role of policy makers, researchers and practitioners involved in the construction, renovation and reuse of the built environment in order to deal with the environmental/ecological, economic/financial, and social/ethical challenges of providing a habitat for current and future generations in a rapidly changing world. These complex challenges are too complex to be dealt with only by one discipline or profession. This book presents and illustrates innovative contributions applied during the planning of built environments, with case studies focusing on five strategic domains and the interrelations between them. These recent contributions apply concepts, methods and tools that enable concerted action between stakeholders collaborating in policy definition and project implementation. These methods and tools include experiments in living-labs, prototypes on site, virtual simulations and agent-based modeling, as well as participatory approaches with citizen science for data collection, the development of alternative scenarios, and visioning plausible futures"--
OCLC-licensed vendor bibliographic record.
Keywords: City planning; Sustainable urban development; Cities and towns -- Technological innovations; Urban ecology (Sociology); Architectural design; ARCHITECTURE / Landscape